Autophagy-dependent EIF2AK3 activation compromises ursolic acid-induced apoptosis through upregulation of MCL1 in MCF-7 human breast cancer cells - Zhao, Chong (Landes Bioscience, 2013)
Ursolic acid (UA) is a pentacyclic triterpenoid with promising cancer chemopreventive properties. A better understanding of the mechanisms underlying anticancer activity of UA is needed for further development as a clinically useful chemopreventive agent. Here, we found that both endoplasmic reticulum (ER) stress and autophagy were induced by UA in MCF-7 human breast cancer cells. Surprisingly, ER stress was identified as an effect rather than a cause of UA-induced autophagy. Autophagy-dependent ER stress protected the cells from UA-induced apoptosis through EIF2AK3-mediated upregulation of MCL1. Activation of MAPK1/3 but not inhibition of MTOR pathway contributed to UA-induced cytoprotective autophagy in MCF-7 cells. Our findings uncovered a novel cellular mechanism involved in the anticancer activity of UA, and also provided a useful model to study biological significance and mechanisms of autophagy-mediated ER stress.